Studi Kelayakan Produksi Wedang Jahe Senja Padam dan Sedayu Manja - Agus Aan Adriansyah; Budhi Setianto; Akas Yekti Pulih Asih; Maya Purnia Sari; Nailah Tri Iswira; Aizatun Nisa; Difran Nobel Bistara; Eppy Setiyowati; Nikmatus Sa’adah; Muhammad Fifin Kombih (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2022)
Ginger as a herbal plant is widely used as a drink and a cooking ingredient, Wedang Senja Padam and Sedayu Manja are drinks served to Covid 19 patients at the Surabaya Islamic Hospital. To increase production capacity as an additional source of income, it is necessary to calculate a feasibility study on the manufacture of Senja Padam and Sedayu Manja drinks. This service begins with conducting a study of the materials to be used in the literature, the amount, and the composition of the ingredients following the drink. Conduct market research related to the results of testing the composition of ingredients on customers. From this service, produce a composition of beverage ingredients following customer desires and produce a feasibility study that provides a positive value of the initial investment value of 2,500,000 resulting in a net cash flow of 6,187,500 with an IRR value of 21% and a B/C of 1.3 showing fit for production.